Properties of CdSe heterolayers obtained by isovalent substitution on CdTe substrates - Makhniy, V.P.; Slyotov, М.М.; Tkachenko, I.V.; Slyotov, А.М. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
Using the isovalent substitution method, CdSe heterolayers of cubic modification were obtained for the first time on single-crystal CdTe substrates, and their basic physical properties were studied.